"We Are the Locals": The Operationalisation of Rights-Based Approaches to Development by Non-governmental Organisations in Koraput District, Odisha. Issue 5 (December 2018) - Mishra, Nita; Lahiff, Edward
Abstract This paper examines programs, strategies and actions adopted by non-governmental organisations in Odisha State and their impact on poverty alleviation and in policy making, from a rights-based approach (RBA) to development. Scholars (Sen in Philos Public Aff 32(4):315–356, 2004; Sengupta in: Pogge (ed) Freedom from poverty as a human right: who owes what to the very poor?, Oxford University Press, Oxford, 2007) argue that, although the state is the primary duty-bearer, human rights induces obligations on agents such as non-governmental organisations that are in a position to help, promote or safeguard the freedoms of human beings. This is a qualitative field study conducted in three districts in Odisha, India. Activities of five non-governmental organisations (NGOs) were selected for this study, and methods used were in-depth interviews and group discussions. Evidence suggests that many NGOs in Odisha find RBA as a political activity, best practised when communities organise themselves around issue-based activities, build capabilities and create alliances at various levels. Cet article étudie les programmes, les stratégies et les actions adoptés par les organisations non gouvernementales dans l'État d'Odisha, ainsi que leur impact sur la réduction de la pauvreté et l'élaboration de politiques selon une approche au développement fondée sur les droits. Les spécialistes (Sen in Philos Public Aff 32(4):315–356, 2004; Sengupta in: Pogge (ed) Freedom from poverty as a human right: who owes what to the very poor?, Oxford University Press, Oxford, 2007) soutiennent que bien que l'État soit le principal responsable, les droits de l'homme imposent des obligations aux agents tels que les organisations non gouvernementales, qui peuvent aider, promouvoir ou sauvegarder les libertés des êtres humains. Il s'agit d'une étude de terrain qualitative menée dans trois districts d'Odisha, en Inde. Les activités de cinq organisations non gouvernementales (ONG) ont été sélectionnées pour cette étude; les méthodes utilisées étaient des entretiens approfondis et des discussions de groupe. Les résultats suggèrent que de nombreuses ONG à Odisha considèrent l'approche fondée sur les droits comme une activité politique qu'il vaut mieux réaliser lorsque les communautés s'organisent pour agir sur leurs problèmes, montent en compétences et créent des alliances à différents niveaux.